Analisis Framing Pemberitaan Minyakita Di Media Daring Serta Rekomendasinya Sebagai Handout Materi Teks Berita Kelas VII SMP - Cahyani, Regita Indah; Syafroni, Roni Nugraha; Suprihatin, Dewi (Peneliti.net, 2024)
The Minyakita brand is a registered trademark for palm cooking oil, owned by the Director General of Domestic Trade under the Ministry of Trade. Since its introduction, Minyakita has gained popularity in the market and has become a widely used cooking oil by the public. The research focuses on the media coverage of Minyakita, specifically analyzing online platforms like Kompas.com, Pikiranrakyat.com, and Tribunnews.com using Zhongdang Pan and Gerald M. Kosicki's framing analysis. The primary objective of this study is to employ Zhongdang Pan and Gerald M. Kosicki's framing analysis on news articles related to Minyakita from January to February 2023, published on Kompas.com, Pikiranrakyat.com, and Tribunnews.com. This analysis is intended to provide insights that can be utilized as instructional content for teaching news text comprehension to seventh-grade junior high school students. A qualitative approach with descriptive methods is employed for this study. Data collection involves observing and noting 15 relevant news articles from the specified time period and media outlets. A framing analysis guide, aligned with Zhongdang Pan and Gerald M. Kosicki's perspectives, is used as the research instrument. Data analysis consists of data reduction, presentation, interpretation, and conclusion drawing. The findings reveal both similarities and differences among the online media platforms. All three platforms adhere to a complete script structure, incorporating the 5W+1H elements and citing the same source. However, discrepancies arise in their thematic structures. Kompas.com, Pikiranrakyat.com, and Tribunnews.com do not share the same wording when emphasizing the news messages. The insights obtained from Zhongdang Pan and Gerald M. Kosicki's framing analysis of the Minyakita news coverage from January to February 2023 in the mentioned online media outlets are recommended for crafting news text handouts suitable for seventh-grade junior high school students. These teaching materials can facilitate the comprehension and analysis of news texts in the classroom setting.